Pengaruh Earning Per Share Dan Dividen Per Share Terhadap Harga Saham Perusahaan Sektor Properti, Real Estate Dan Konstruksi Yang Terdaftar Di BEI - Desy Sulistiawati; Herman Sjahruddin (Universitas Respati Indonesia, 2020)
We try to explain the effect of earnings per share and dividends per share on the stock prices of property, real estate and construction sector companies listed on the Indonesia Stock Exchange. The population in this study were 82 property, real estate and construction sector companies listed on the Indonesia Stock Exchange. The sample uses a purposive sampling method, there are 16 companies as samples (66 companies, did not meet the criteria and the data are considered inappropriate). The analytical tool used is multiple linear regression analysis which aims to analyze the effect between earnings per share variable and dividend per share on stock prices using SPSS v.25 software. The results showed evidence that earnings per share had a significant positive effect and dividends per share had a positive and not significant effect on stock prices (closing price).